A Model for Improving MSME Competitiveness and Performance: The Impact of Digital Marketing, Product Innovation, and Market Orientation in The Creative Industry Sector in Southwest Sumba Regency - Merlyn Kurniawati; Yuri Sandra Faah; Efandri Agustian; Familya Maria D.L. Moensaku (Dinasti Publisher, 2025)
The existence of creativity-based MSMEs has significant potential for creating jobs, encouraging innovation and entrepreneurship, increasing regional income, strengthening local cultural identity, and contributing to overall economic growth through the utilization of human resources and creative ideas. The increasing number of MSMEs operating in the creative industry sector inevitably creates increasingly fierce competition. MSMEs must be able to improve their competitiveness and business performance through product innovation, marketing digitalization, and effective market orientation. The purpose of this study is to develop a model for improving the competitiveness and performance of MSMEs in the creative industry sector in Southwest Sumba Regency, East Nusa Tenggara, through three main constructs: digital marketing, product innovation, and market orientation. Data analysis was conducted using descriptive qualitative methods by systematically compiling data/information obtained from field research in the form of interviews, field notes, and documentation. The data was organized into categories to facilitate analysis. The research informants consisted of creative industry business actors, local government officials, and digital marketing practitioners. The research results show that the creative industry in Southwest Sumba Regency has superior potential, especially in the craft sub-sector (woven fabrics, handicrafts, and jewelry made from beads and metal), which combines local cultural values ​​with commercial aesthetics. However, business actors face challenges in expanding markets, improving product quality, and adopting effective digital marketing strategies. Adopting digital marketing and product innovation, combined with a strong market orientation, can improve the competitiveness and performance of MSMEs in Southwest Sumba Regency.